1987
DOI: 10.3109/10408418709104443
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Halotolerance in Microorganisms

Abstract: Microorganisms have the ability to adapt to a wide range of NaCl concentrations. In general the NaCl tolerance shown by microbes far exceeds the salt tolerance of any other organism, procryote or eukaryote. There are at least three mechanisms available for adaptation to different salt concentrations. The first would be a passive one in which the cytoplasmic ion content would always equal that in the medium. A second mechanism which is used by many organisms involves concentrating compatible solutes to create a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 81 publications
1
82
0
2
Order By: Relevance
“…As high amounts of these solutes are required for further research into possible applications, these data are of importance for the possible selection of producer strains. Although halophilic heterotrophic aerobic eubacteria have been the objects of research for several decades (Rodriguez-Valera, 1988 ;Vreeland, 1987 ;Kushner, 1988;Kushner & Kamekura, 1988), their mechanism of osmoadaptation has remained obscure. Neither inorganic ions nor organic molecules were detected in sufficiently high intracellular concentrations to balance the low external water activity.…”
Section: Separation and Quantijication Of Organic Osmolytes By Hplcmentioning
confidence: 99%
“…As high amounts of these solutes are required for further research into possible applications, these data are of importance for the possible selection of producer strains. Although halophilic heterotrophic aerobic eubacteria have been the objects of research for several decades (Rodriguez-Valera, 1988 ;Vreeland, 1987 ;Kushner, 1988;Kushner & Kamekura, 1988), their mechanism of osmoadaptation has remained obscure. Neither inorganic ions nor organic molecules were detected in sufficiently high intracellular concentrations to balance the low external water activity.…”
Section: Separation and Quantijication Of Organic Osmolytes By Hplcmentioning
confidence: 99%
“…The consequences are changing cellular volume and turgor pressure that exert strong mechanical forces on the cytoplasmic membrane and associated proteins and, if too high, preclude growth of the bacterium and eventually cause cell death 1 . To cope with osmotic stress, bacteria evolved several strategies such as adapting their intracellular osmolality [2][3][4] or increasing their cell wall stability 5 , allowing them to grow in a broad range of solute concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…antiporter to maintain a large Na ? gradient in the cytoplasm (Vreeland 1987). Within the CC, three of the strains, Pseudomonas fluorescens (Viggor et al 2013), Brevundimonas and Stenotrophomonas (Mahjoubi et al 2013) may possess such mechanism since they were reported in other studies to survive in the sea and marine environments.…”
Section: Resultsmentioning
confidence: 99%
“…Vreeland (1987) reported strains could adapt to high salinity by concentrating compatible solutes to create an osmotic balance between the cytoplasm and the external environment or by altering membrane permeability to control the movement of water and allowing the cell to exist with an ionically dilute cytoplasm. Some bacterial strains can lower its cytoplasmic ionic content compared with the outside medium by activating a Na ?…”
Section: Resultsmentioning
confidence: 99%